Case Report: Pituitary metastasis from prostate adenocarcinoma: an integrated diagnosis via 68Ga-PSMA PET/CT and methylome analysis - N. Bianchetto Wolf; I. C. Mainta; A. Fitsiori; G. Colarusso; P. Tsantoulis; K. L. Egervari; V. Garibotto (Frontiers in Medicine)
BackgroundPituitary metastases are rare, accounting for only 1% of all pituitary tumor resections. Prostate adenocarcinoma, a common malignancy in men, seldom metastasizes to the pituitary gland, with only a few reported cases. Given their rarity and non-specific clinical presentation, pituitary metastases are often mistaken for primary sellar lesions. Advanced imaging techniques, including Prostate-Specific Membrane Antigen (PSMA) positron emission tomography (PET)/Computed Tomography (CT) and molecular diagnostics, such as DNA methylation profiling, can aid in accurate diagnosis and differentiation from pituitary adenomas.Case presentationWe report the case of a 71-year-old male with a history of prostate adenocarcinoma who presented with biochemical recurrence and underwent PSMA PET/CT imaging, revealing intense tracer uptake in the pituitary gland. Magnetic Resonance Imaging (MRI) findings were suggestive of a pituitary macroadenoma, and the patient developed bitemporal hemianopia, necessitating transsphenoidal surgical resection. Histopathological and immunohistochemical analyses were not compatible with a primary pituitary lesion, prompting further investigation via DNA methylation profiling. The analysis revealed a DNA-methylation signature consistent with prostate carcinoma, confirming pituitary metastasis. The patient subsequently received systemic treatment with androgen deprivation therapy, abiraterone, and docetaxel, achieving an excellent biochemical and imaging response.ConclusionThis case highlights the importance of considering metastatic prostate cancer in the differential diagnosis of pituitary lesions, particularly when PSMA PET/CT shows focal uptake in atypical locations. Integration of histopathological, immunohistochemical, and molecular techniques, such as DNA-methylation profiling, was essential for confirming the diagnosis. Clinicians should remain vigilant for atypical metastatic presentations and leverage advanced diagnostic tools to ensure accurate diagnosis and optimal patient management.